1990
DOI: 10.1192/bjp.156.6.846
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in Violence on an Acute Psychiatric Ward

Abstract: The increase in violent incidents on an acute psychiatric ward over a 15-month period was found to be strongly associated with the increase in use of temporary nursing staff (r = 0.63; P = 0.0005). The change in staffing patterns accounted for 39% of the variance in violence. An examination of the characteristics of all patients admitted to the ward revealed that the violent patients were significantly younger, more likely to have been admitted compulsorily and less likely to be depressed than non-violent ones. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
119
2
6

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(146 citation statements)
references
References 26 publications
19
119
2
6
Order By: Relevance
“…There is considerable agreement in the literature that ward culture (Katz & Kirkland, 1990), and wards with less bstableQ patients (e.g., admission and locked wards) are most often the site of violence (Fottrell, 1980;Hodgkinson et al, 1985;Katz & Kirkland, 1990;Nijman, Allertz, à Campo, Merckelbach, & Ravelli, 1997). In several studies, it was reported that patients admitted involuntarily under mental health legislation were significantly more likely to be engaged in violent acts (Delaney, Cleary, Jordan, & Horsfall, 2001;James, Fineberg, Shah, & Priest, 1990;Owen, Tarantello, Jones, & Tennant, 1998;Powell, Caan, & Crowe, 1994;Soliman & Reza, 2001). In some studies, it was concluded that attacks often occurred when nurses were administering medication or leading or restraining agitated patients (Kalogjera, Bedi, Watson, & Meyer, 1989;Morrison et al, 2002;Soloff, 1983;Wynn, 2003).…”
Section: Determinants Of Aggressionmentioning
confidence: 99%
“…There is considerable agreement in the literature that ward culture (Katz & Kirkland, 1990), and wards with less bstableQ patients (e.g., admission and locked wards) are most often the site of violence (Fottrell, 1980;Hodgkinson et al, 1985;Katz & Kirkland, 1990;Nijman, Allertz, à Campo, Merckelbach, & Ravelli, 1997). In several studies, it was reported that patients admitted involuntarily under mental health legislation were significantly more likely to be engaged in violent acts (Delaney, Cleary, Jordan, & Horsfall, 2001;James, Fineberg, Shah, & Priest, 1990;Owen, Tarantello, Jones, & Tennant, 1998;Powell, Caan, & Crowe, 1994;Soliman & Reza, 2001). In some studies, it was concluded that attacks often occurred when nurses were administering medication or leading or restraining agitated patients (Kalogjera, Bedi, Watson, & Meyer, 1989;Morrison et al, 2002;Soloff, 1983;Wynn, 2003).…”
Section: Determinants Of Aggressionmentioning
confidence: 99%
“…These factors were more likely to be male, less than 45 years old, and those from diagnosis of schizophrenia (Chukwujekwu & Stanley, 2011;Pearson et al, 1986) use of temporary nursing staff (James, Fineberg, Shah, & Priest, 1990); previous aggressive and disturbed behavior (Noble & Rodger, 1989); criminal record and previous drug abuse (Walker & Seifert, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This of course is just one way in which interpersonal stability could be reduced on a ward. In fact, from the perspective of a service user, interpersonal stability may be compromised by a host of factors which might include inter alia deterioration in their own mental state (Watson et al, 2007), variability in the mental state of other service users, high turnover in primary care staff (James et al, 1990), by high stress levels in primary care staff (Gray-Toft et al, 1981), or, by inconsistency in how staff perceive and react to their attachment needs. The focus here will be on the last of these potential hazards for relational security, it has been demonstrated that staff ratings of service user attachment styles can be inconsistent (Bagshaw et al, 2012) even within a medium secure service that aimed to apply ideas drawn from Attachment Theory to plan nursing care .…”
mentioning
confidence: 99%
“…The capacity for medium secure units (MSUs) to deliver physical security is almost beyond question, they provide very controlled environments with high levels of service user observation and robust systems for physical containment and for controlling untoward behavior. Apart from the physical and procedural aspects of security, the stability of the interpersonal environment that staff provide has been shown to be important for reducing service user violence (James et al, 1990) and it is reasonable to suppose that consistent therapeutic rapport will also facilitate other aspects of service user recovery. report the benfits of changing nursing observation levels within a female medium secure ward in accordance with a flexible, nurse-led model for managing service user self-harm that was informed by attachment theory.…”
mentioning
confidence: 99%
See 1 more Smart Citation